An iron–based biochar for persulfate activation with highly efficient and durable removal of refractory dyes. Issue 1 (February 2022) - Guo, Lijun; Zhao, Liming; Tang, Yuling; Zhou, Jianfei; Shi, Bi
Abstract: The magnetic biochar catalyst (Fe@BC) was synthesized by pyrolyzing Fe–tanned collagen fiber based on the tanning process and used as a high–efficiency and recyclable persulfate (PS) activator to degrade refractory dyes. In this study, methylene blue (MB) was chosen as a model pollutant to evaluate the performance of the Fe@BC/PS system. Results illustrated that MB was completely removed within 20 min with a rate constant (kobs ) of 0.2246 min – 1, which was much higher than that of pure biochar (0.0497 min – 1 ), and high mineralization efficiency (92%) for MB degradation was obtained. Notably, the MB removal rate still reached 72% after 20 cycles. The high catalytic activity and excellent recycling performance could be attributed to the uniformly dispersed iron species, abundant oxygen functional groups, and defective carbon matrix. Radical quenching experiments and electron paramagnetic resonance studies illustrated that SO4 – was the predominant free radical for MB degradation. Moreover, other refractory dyes could also be rapidly and efficiently removed from the Fe@BC/PS system. This work is expected to propose a promising catalyst for the degradation of refractory dyes and open a new possibility for the durable removal of refractory organic dyes. Graphical Abstract: ga1 Highlights: The magnetic biochar (Fe@BC) was prepared using collagen fiber as a matrix. Fe@BC/PS showed a good mineralization rate of 92% towards methylene blue. An excellent degradation efficiency of 90% was achieved after 15 cycles. The uniformly dispersed iron on Fe@BC promoted PS activation. Fe@BC/PS was fit for dye removal because the sharply reduced ecotoxicity.